Across the consciousness continuum—from unresponsive wakefulness to sleep - Blume, Christine; del Giudice, Renata; Wislowska, Malgorzata; Lechinger, Julia; Schabus, Manuel (Frontiers in Human Neuroscience, 2015)
Advances in the development of new paradigms as well as in neuroimaging techniques nowadays enable us to make inferences about the level of consciousness patients with disorders of consciousness (DOC) retain. They moreover allow predicting their probable development. Today, we know that certain brain responses (e.g. event-related potentials or oscillatory changes) to stimulation, circadian rhythmicity, the presence or absence of sleep patterns as well as measures of resting state brain activity can serve the diagnostic and prognostic evaluation process. Still, the paradigms we are using nowadays do not allow to disentangle VS/UWS and MCS patients with the desired reliability and validity. Furthermore, even rather well-established methods have unfortunately not found their way into clinical routine yet. We here review current literature as well as preliminary findings and discuss how neuroimaging methods (fMRI, PET) and particularly EEG can be used to investigate cognition in DOC or even to assess the degree of residual awareness. We, moreover, propose that circadian rhythmicity and sleep in brain-injured patients are promising fields of research in this context.